Prototyping Aplikasi E-Health sebagai Bagian Pengenalan Obat-Obatan Dengan Teknologi Cross-Platform - Ari Muzakir (Politeknik Harapan Bersama, 2018)
Nowadays peoples usually do various ways to know the types and benefits of medicines to solve their symptoms. For example they do search information through Internet, but they don’t know the appropriate drug to consume according their symptoms. This research aimed to build an encyclopedia about E-Health-based drugs. By utilizing encyclopedia about E-Health-based drugs, its much easier to most peoples to understand and recognize various types of medicines including herbal and chemical medicines. The result of this research is an application prototype about encyclopedia of E-Health-based drugs that runs on web and mobile platforms tested by blacbox method. Furthermore, the result of this research, can be a basis to develop a larger and functional E-Health-based drugs encyclopedia modules.